(untitled) (Manabia: Journal of Constitutional Law, 2025)
Motorcycles are not included in the category of public transportation as regulated in Law Number 22 of 2009 concerning Traffic and Road Transportation. This is reinforced by the Constitutional Court Decision Number 41/PUU-XVI/2018. However, the Minister of Transportation Regulation Number 12 of 2019 actually regulates motorcycles used for the benefit of the community, a term that is functionally equivalent to public transportation. The purpose of this study is to analyze the inconsistencies that occur between the Minister of Transportation Regulation Number 12 of 2019 and Law Number 22 of 2009, as well as the legal consequences arising from such inconsistency. This study utilizes a normative/legal research method. The approach used is the statutory approach and the conceptual approach. The author uses a prescriptive analysis to examine the research by constructing arguments based on findings using deductive reasoning. The results indicate that the inconsistency between Minister of Transportation Regulation Number 12 of 2019 and Law Number 22 of 2009 occurs hierarchically, substantively, and implementatively. Furthermore, there is a discrepancy between the formation of the ministerial regulation and the principles of proper legislation as regulated in Law Number 12 of 2011. Consequently, the legal implications of this inconsistency include legal uncertainty, potential legal disputes, and a decline in public trust toward the government.